Affiliation With Antisocial Crowds and Psychosocial Outcomes in a Gang-Impacted Urban Middle School. (April 2017) - Schwartz, David; Hopmeyer, Andrea; Luo, Tana; Ross, Alexandra C.; Fischer, Jesse
This longitudinal study examined the psychosocial adjustment of adolescents who affiliate with antisocial crowds in a gang-impacted urban environment. We followed 405 adolescents (219 boys, 186 girls; average age of 11.51 years, SD = .61; 84% Latino, 9% Asian, and 7% other or unclassified) for one academic year. These youth attended a middle school located in an economically distressed neighborhood with documented high rates of gang violence. We assessed crowd membership with a structured focus group procedure. In addition, we administered a peer nomination inventory to assess aggression and social standing, obtained self-reports of depressive symptoms, and derived grade point averages (GPA) directly from school records. Adolescents used gang-related imagery to describe antisocial crowds in their school, referring to "cholos" and "taggers." Membership in these crowds was associated with aggression and low GPA but, paradoxically, predicted small decreases in depression and increases in popularity over time. Taken together, our results highlight the complex role of affiliations with antisocial crowds in high-risk settings.